Efficient Iterative Method for Solving Korteweg-de Vries Equations - yassein, samaher marez; Aswhad, Asmaa Abd (Iraqi Journal of Science, 2019)
The Korteweg-de Vries equation plays an important role in fluid physics and applied mathematics. This equation is a fundamental within study of shallow water waves. Since these equations arise in many applications and physical phenomena, it is officially showed that this equation has solitary waves as solutions, The Korteweg-de Vries equation is utilized to characterize a long waves travelling in channels. The goal of this paper is to construct the new effective frequent relation to resolve these problems where the semi analytic iterative technique presents new enforcement to solve Korteweg-de Vries equations. The distinctive feature of this method is, it can be utilized to get approximate solutions for travelling waves of non-linear partial differential equations with small amount of computations does not require to calculate restrictive assumptions or transformation like other conventional methods. In addition, several examples clarify the relevant features of this presented method, so the results of this study are debated to show that this method is a powerful tool and promising to illustrate the accuracy and efficiency for solving these problems. To evaluate the results in the iterative process we used the Matlab symbolic manipulator.